Culture and its influence on an increase of cervical cancer cases in Angola - João Wilson da Rocha (Brazilian Journal of Oncology)
Cervical cancer is the second most common cancer among women worldwide and also in Angola. Its highest incidence occurs in women between 45 and 55 years of age; the main etymological factor is the infection with human papilloma virus (HPV), whose DNA is detectable in more than 99% of cases. This article review demonstrates some sociocultural, socio-economic, ethnic, and linguistic factors as influencing the increase of cervical cancer cases in Angola.